Evaluation of antioxidant properties of Za’atar (Thymbra spicata) essential oils as natural antioxidant for stability of palm olein during deep-fat frying process - Maskan, Medeni (J Food Sci Technol, 2017)
The yield of Za’atar (Thymbra spicata) essential oils were found to be 2.5–3.4% at extraction process temperatures of 100–175 °C. The essential oils contained 79.5–86.2% carvacrol. Effects of BHT and Za’atar essential oil on stability of palm olein during deep-fat frying of potato slices were studied at 180 °C. Changes in peroxide, para-anisidine, iodine values, free fatty acid and color were determined. Za’atar essential oil and BHT reduced free fatty acid content of olein from 0.27 to 0.21% (oleic acid) after 50 frying cycles. Antioxidant addition did not change the peroxide value of oil. Frying decreased Hunter L value and increased a, b, and total color difference values of used oils. The P-anisidine value changed from 15 to 33 for control oil during frying. BHT and Za’atar essential oil reduced this value to 28. The iodine values of olein reduced from an initial value of 54.5 to 45, 49 and 49 for control, BHT and Za’atar essential oil added frying oils, respectively. Za’atar essential oils could be used for preserving palm olein during deep-fat frying process.